Diet and Exposure of Sources of Information As A Contributing Factor to Diabetes Mellitus Type II Disease in Kendari City - Siti Umrana; Risnawati Risnawati (KLASICS, 2021)
Diabetes Mellitus is also known as a disease related to food intake, both as a causal factor and treatment. Diabetes is increasing every year. The worldwide commonness of Diabetes among grown-ups is expanding and happening quicker in the center world. Until 2020 when the age of the Indonesian population over 20 years reached the number of 178 million people and assuming the number of people with Diabetes Mellitus 4%, the proportion of cases of Diabetes Mellitus from 2018 to 2019 increased to 2546 cases from all Community Health Center in Kendari City. This analysis could be a sort of quantitative analysis with a cross-sectional style. The population in this study is all new cases of Diabetes Mellitus patients who conducted examinations or treatment at the Labibia Health Center Kendari city as many as 107 people and samples in this study took 52 people with accidental sampling techniques. The statistical test used was Chi-square with a 95% confidence level. The results showed that the diet about diabetes mellitus in the sufficient category was 19.2%, and the less category was 80.8%. In comparison, the exposure to sources of information about diabetes mellitus in the sufficient category was 46.2%, and the less category was 53.8%. The analysis results also show a significant relationship between diet and Diabetes Mellitus, as evidenced by the p-value = 0.036 ( = 0.05), and exposure to information sources with Diabetes Mellitus as evidenced by the p-value = 0.012 ( = 0.012 value). 0.05). Keywords: diet, exposure to information sources, diabetes mellitus.